2009
DOI: 10.1016/j.cell.2008.12.022
|View full text |Cite
|
Sign up to set email alerts
|

SEPA-1 Mediates the Specific Recognition and Degradation of P Granule Components by Autophagy in C. elegans

Abstract: How autophagy, an evolutionarily conserved intracellular catabolic system for bulk degradation, selectively degrades protein aggregates is poorly understood. Here, we show that several maternally derived germ P granule components are selectively eliminated by autophagy in somatic cells during C. elegans embryogenesis. The activity of sepa-1 is required for the degradation of these P granule components and for their accumulation into aggregates, termed PGL granules, in autophagy mutants. SEPA-1 forms protein ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
331
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(339 citation statements)
references
References 20 publications
4
331
0
4
Order By: Relevance
“…Lifespan extension in daf-2 mutants has also been reported to require the autophagy pathway, which operates in a DAF-16-independent manner to recycle proteins and organelles (30,31). Interestingly, P granules are normally removed from the somatic blastomeres in embryos through autophagy (32), which likely clears them from the somatic cells of daf-2 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Lifespan extension in daf-2 mutants has also been reported to require the autophagy pathway, which operates in a DAF-16-independent manner to recycle proteins and organelles (30,31). Interestingly, P granules are normally removed from the somatic blastomeres in embryos through autophagy (32), which likely clears them from the somatic cells of daf-2 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The first demonstrated that in C. elegans autophagy mutants, P-granule components erroneously formed foci in somatic cells. 80 A selective autophagy mechanism, depending on interaction of P-granule factors with the protein SEPA-1, was identified that helps clear formation of these aberrant foci. 81 Similarly, stress granules can accumulate in yeast and mammalian cell autophagy mutants, and are targeted by autophagy under various growth and stress conditions.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…For example, abnormalities in larval development, synapse formation, and eye development are observed in autophagy gene mutant Drosophila. [8][9][10][11][12] In C. elegans, autophagy genes play a role in apoptotic corpse clearance in embryonic development, 13 the L1 larval stage, 14 and the adult gonad, 15 in degrading germline P granules in somatic cells, 16 and in the selective elimination of paternal mitochondria. 17,18 In mice, autophagy genes play an essential role in preimplantation development, survival during the neonatal starvation period, and in the differentiation of several specific cell lineages, including adipocytes, erythrocytes, and lymphocytes (T cells and B-1a cells) (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%